2019
DOI: 10.1002/hed.26038
|View full text |Cite
|
Sign up to set email alerts
|

Comparing postoperative outcomes after free flap surgery in a specialty step‐down unit vs nonspecialty intensive care unit

Abstract: Background To determine if there was a difference in postoperative outcomes of head and neck free flap reconstruction patients treated in a specialty step‐down unit compared to a nonspecialty intensive care unit (ICU). Methods A retrospective review was performed of all patients who underwent free flap reconstruction for head and neck defects from 2014 to 2017 at Loyola University Medical Center. Patients managed postoperatively in the ICU were compared to patients managed in a specialty step‐down unit. Postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Indeed, at our institution, microvascular breast reconstruction patients are never admitted to the intensive care unit for the sole purpose of flap monitoring. A number of retrospective studies [32][33][34] and a prospective randomized trial 35 identified that intensive care unit care was associated with equivalent outcomes compared to non-intensive care unit care and that a significant cost savings was realized for flap patients admitted to lower acuity settings. In fact, one study found that the cost of 3 days of intensive care unit care averaged $4449 per day-71 percent more than the daily cost of the standard floor-bed in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, at our institution, microvascular breast reconstruction patients are never admitted to the intensive care unit for the sole purpose of flap monitoring. A number of retrospective studies [32][33][34] and a prospective randomized trial 35 identified that intensive care unit care was associated with equivalent outcomes compared to non-intensive care unit care and that a significant cost savings was realized for flap patients admitted to lower acuity settings. In fact, one study found that the cost of 3 days of intensive care unit care averaged $4449 per day-71 percent more than the daily cost of the standard floor-bed in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cervenka et al 17 reported no significant difference between ICU and non-ICU nursing regarding THC. Yang et al 20 stated that THC is about 35% higer in the patients admitted to ICU. Panwar et al 11 and Yalamanchi et al 22 reported a statistically significant difference between ICU and non-ICU caring p<0.001 and 0.00054, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to the existing literature, ICU care fee reported to be accounted for about 35% of the total hospital cost. 20 Therefore, admission to non-ICU care could reduce the high cost of ICU services and facilitates the management of available resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Adherence to data-driven ICU admission and discharge criteria may reduce unindicated utilization by patients with low preoperative risk scores. Caring for select patients in step-down units rather than ICU beds, such as those undergoing free-flap reconstructions 6 or those requiring insulin infusions, 7 may also reduce bottlenecks for patient flow without compromising outcomes.…”
mentioning
confidence: 99%